Hotel co-branding: Is 2 better than 1? - Chong, Daniel Ka Leong * (Tourism Educatiors Association of Malaysia, 2017)
This study aims to examine the effectiveness of co-branding strategy in improving the hotel’s perceived service tangibility. The existing literature on improving service tangibility was found little and there are relatively little effort has been made to explore co-branding effect in tangibilizing services. Methodologically, the development of hypotheses was constructed base on the concept of service tangibilization dimensions by Laroche et al (2003). Primary Data has been collected through the use of a questionnaire. In analysis, the gaps between co-branded and standalone hotel’s brand were measured. Empirical findings showed that co-branding is positively related to the perceived tangibility of the hotel service. Interestingly, the perception of service tangibility is hardly seen as a result of the brands synergy but mainly the interpretation of the dominant brand in the partnership. These findings suggest that the act of pairing with a product brand may lend credibility to a service brand, even when one or both of those constituent brands are perceived as having low brand equity. Hence, brand partnership should be considered by hotel branding managers in pursue of better market recognition in relation to product and services positioning.